Of Mice, Men, and Trolleys: Hypothetical Judgment Versus Real-Life Behavior in Trolley-Style Moral Dilemmas - Bostyn, Dries H.; Sevenhant, Sybren; Roets, Arne (Psychological Science, 2018)
Scholars have been using hypothetical dilemmas to investigate moral decision making for decades. However, whether people’s responses to these dilemmas truly reflect the decisions they would make in real life is unclear. In the current study, participants had to make the real-life decision to administer an electroshock (that they did not know was bogus) to a single mouse or allow five other mice to receive the shock. Our results indicate that responses to hypothetical dilemmas are not predictive of real-life dilemma behavior, but they are predictive of affective and cognitive aspects of the real-life decision. Furthermore, participants were twice as likely to refrain from shocking the single mouse when confronted with a hypothetical versus the real version of the dilemma. We argue that hypothetical-dilemma research, while valuable for understanding moral cognition, has little predictive value for actual behavior and that future studies should investigate actual moral behavior along with the hypothetical scenarios dominating the field.